2009
DOI: 10.1111/j.1440-1819.2008.01921.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroleptic malignant syndrome with use of quetiapine in mental retardation

Abstract: alone or depression alone. Persons with PTMD are more impulsive-aggressive and more suicidal compared to individuals with PTSD alone or depression alone. 5 Further studies of aggression, impulsivity and suicidality in psychiatric patients, especially in individuals with depressive and stress-related disorders, may produce important and interesting results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Accurate and timely diagnosis of NMS is vital to ensure appropriate treatment in hospital is instigated to reduce the high risk of death. NMS is associated with FGA but there is a growing evidence of NMS following treatment with second-generation antipsychotics such as Quetiapine [22,23].…”
Section: Neuroleptic Malignant Syndromementioning
confidence: 99%
“…Accurate and timely diagnosis of NMS is vital to ensure appropriate treatment in hospital is instigated to reduce the high risk of death. NMS is associated with FGA but there is a growing evidence of NMS following treatment with second-generation antipsychotics such as Quetiapine [22,23].…”
Section: Neuroleptic Malignant Syndromementioning
confidence: 99%
“…Accurate and timely diagnosis of NMS is vital to ensure appropriate treatment in hospital is instigated to reduce the high risk of death. NMS is associated with FGA but there is a growing evidence of NMS following treatment with second-generation antipsychotics such as Quetiapine [22,23].…”
Section: Neuroleptic Malignant Syndromementioning
confidence: 99%
“…8 As to adverse effects of treatments, Dan et al reported a case of severe mental retardation in a 20-year-old man who had a fatal outcome of neuroleptic malignant syndrome caused by quetiapine used to control his frequent unprovoked aggression. 9 Kato et al reported a case of schizophrenia in a 24-year-old woman in whom tardive dystonia developed after risperidone administration was improved by switching risperidone to aripiprazole. 10 Echizenya et al noted that adolescents with freerunning disorder (non-24-h sleep-wake syndrome) have a risk of developing a paradoxical reaction when they take hypnotics based on two such cases…”
Section: P Sychiatry and Clinical Neurosciencesmentioning
confidence: 99%
“…As to adverse effects of treatments, Dan et al . reported a case of severe mental retardation in a 20‐year‐old man who had a fatal outcome of neuroleptic malignant syndrome caused by quetiapine used to control his frequent unprovoked aggression 9 . Kato et al .…”
mentioning
confidence: 99%